Biopsychosocial Characteristics of offender Children Sent for Distingushing and Discretion - Bilgin, Nursel Gamsız; Avcı, Ayşe; Çekin, Necmi; Savran, Bülent (The Bulletin of Legal Medicine, 2001)
Sociodemographic characteristics of offender children, risk factors of crime and psychiatric problems of offender children have been participated in many studies until now. The aims of this study were to determine sociodemograp- hic characteristics and relationships between sociodemographic characteristics and level of depression, anxiety and self-esteem of offender children who were sended the Department of Adana Chairmanship of Forensic Medicine Council. 60 children and adolescent aged between 11-15 (57 boys, 3 girls) years who were offender were included in this study. At the first interview, Sociodemographic data of children were recorded and Beck Depression Inventory (BDI), State and Trait Anxiety ineventory for children (STAI-C) and Piers-Harris-Self Esteem scale were administered to 29 children. The most frequent age was 13 (38.3%). 30% of crime was theft, 85%of crime was assault. The mean age of mothers was 41.6±6.6, 39 of them (%65) did not have any education, 90% of mothers were housewife. The mean age of fathers was 46.5 ±7. 16 of them (%26.7) did not have any education and 43 (71.7%) of fathers were labourer. All of the datas are discussed according to other studies.Key words: Distinguishing and discretion, offender children, beck depression inventory
Keywords: distinguishing and discretion; offender children; beck depression inventory